2016
DOI: 10.1038/srep32554
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 amplifies acetaldehyde-mediated cardiomyocyte mitochondrial dysfunction in alcoholic cardiomyopathy

Abstract: Alcoholic cardiomyopathy (ACM) resulting from excess alcohol consumption is an important cause of heart failure (HF). Although it is assumed that the cardiotoxicity of the ethanol (EtOH)-metabolite acetaldehyde (ACA) is central for its development and progression, the exact mechanisms remain obscure. Murine cardiomyocytes (CMs) exposed to ACA or EtOH showed increased superoxide (O2•−) levels and decreased mitochondrial polarization, both being normalized by NADPH oxidase (NOX) inhibition. C57BL/6 mice and mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 61 publications
2
35
1
Order By: Relevance
“…Jia et al () demonstrated the occurrence of mitochondrial dysfunction in human ARPE19 cells exposed to 50 μM acrolein, also the depletion in mitochondrial potential was time dependent. Further, studies have shown earlier that, activation of NOX2 initiates and enhances mitochondrial and nuclear DNA damage (Brandt et al, ). Excess ROS production by NOX2 triggers the downstream P38MAPK signal which activates both apoptotic and necrotic pathways (Daiber et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Jia et al () demonstrated the occurrence of mitochondrial dysfunction in human ARPE19 cells exposed to 50 μM acrolein, also the depletion in mitochondrial potential was time dependent. Further, studies have shown earlier that, activation of NOX2 initiates and enhances mitochondrial and nuclear DNA damage (Brandt et al, ). Excess ROS production by NOX2 triggers the downstream P38MAPK signal which activates both apoptotic and necrotic pathways (Daiber et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Left ventricular wall thickness, left ventricular end‐diastolic and end‐systolic volumes, left ventricular end‐diastolic and end‐systolic internal diameter, left ventricular ejection fraction, and left ventricular shortening fraction were determined. Some important parameters, including body temperature, heart rate, and anesthesia, were meticulously controlled to minimize iatrogenic effects on the murine cardiac physiology (Brandt et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, feeding animals with Lieber–DeCarli alcoholic liquid diets is a classical method for creating animal models of ACM (Brandt et al., ; Lieber and DeCarli, ; Tan et al., ). Compared with drinking alcohol‐containing water or oral gavage diet, feeding animals only with Lieber–DeCarli alcoholic liquid diets may be more suitable for the evaluation of chronic alcohol exposure (Bertola et al., ; Matyas et al., ).…”
mentioning
confidence: 99%
“…Recent studies show that ALDH-2 plays an important role in the reduction of myocardial damage during ischemia/reperfusion thereby reducing the infarct size [72] and confers cardio-protection in an experimental diabetes/myocardial infarction model [73]. ALDH-2 deficiency was associated with increased ROS formation in aging animals [74], alcohol-induced heart failure [75] and acetaldehyde overload as well as nitroglycerin challenges [76]. In the setting of nitroglycerin-induced nitrate tolerance oxidatively triggered proteasomal degradation of ALDH-2 protein was reported [77].…”
Section: Discussionmentioning
confidence: 99%